A Cross-Cultural Comparison of Domestic American and International Chinese Students’ Social Media Usage - Xu, Qiong; Mocarski, Richard (Journal of International Students, 2014)
This survey of American and Chinese students at a state university in the southern United States measures Social Media (SM) use and attitudes toward SM. The purpose of this study was to investigate student perception and motivation of social media communication and the relationship between student cultural values and their social media participation. The implications of students’ social media participation to an international community were also explored in this study. Foregrounded in the analysis is the role that academic services play in domestic and international students’ scholastic experience, and what SM functions students’ use to engage with these services. The contribution of this study, beyond being one of the first to look at the difference between international and domestic students’ SM patterns, includes a call for the further nuancing of the construct of culture, where culture is dynamic and temporal, instead of just country of origin.